FRMD8 inhibits tumor metastasis in BRCA1-associated TNBC by negatively regulating tmTNF-α - Jun Xu; Xiaoyu Yang; Peng Shu; Wei Wang; Haibo Wu; Zhe Wang (Cellular & Molecular Biology Letters)
Abstract Triple-negative breast cancer (TNBC), particularly in patients with metastasis, is associated with limited treatment options and shorter survival times. In this study, through library screening and animal experiments, we identified that the low expression of FERM domain-containing protein 8 (FRMD8) in breast cancer type 1 susceptibility protein (BRCA1)-mutant breast cancer cells (TNBC subtype), significantly enhances the metastatic potential of tumor cells to various organs. Further functional experiments revealed that FRMD8 low inhibited the cleavage of tmTNF-α (transmembrane TNF-α) and promoted the expression of surface tmTNF-α. We also identified that the mechanism by which FRMD8 regulates tmTNF-α is related to the inhibition of inactive rhomboid protein 2 (iRHOM2) degradation, which acts mainly through the endocytic pathway. Furthermore, FRMD8 low/iRHOM2 low greatly facilitated the in vivo metastasis of TNBC. Finally, we found that combined treatment with paclitaxel and etanercept reversed the expression of FRMD8 and iRHOM2, concomitantly inhibiting the metastatic potential in vivo. This study explores how FRMD8 influences TNF-α processing and the metastatic behavior of breast cancer, providing insights into molecular dynamics that could guide future therapeutic strategies to improve outcomes in patients with breast cancer. Graphical Abstract